Activation of Ceramidase and Ceramide Kinase by Vanadate via a Tyrosine Kinase-Mediated Pathway - Eiko Tada; Kaori Toyomura; Hiroyuki Nakamura; Hirotsune Sasaki; Takeshi Saito; Masayuki Kaneko; Yasunobu Okuma; Toshihiko Murayama (Elsevier, 2010)
Abstract.: Ceramide, a key molecule in the metabolism of sphingolipids, is converted by ceramidase to sphingosine, and phosphorylated by ceramide kinase to form ceramide-1-phosphate (C1P). In this study, we improved on a method of thin-layer chromatography using a fluorescent ceramide, 4-nitrobenzo-2-oxa-1,3-diazole-labeled C6-ceramide (NBD-ceramide) by adding another step for separation of extracted ceramide metabolites by lipophilicity, and determined levels of C1P, caproic acid, sphingomyelin, and glucosylceramide simultaneously. Also we found that 1) treatment of NBD-ceramide-labeled cells (human lung adenocarcinoma A549 cells and Chinese hamster ovary cells) with Na3VO4 increased the amount of NBD-C1P formed within 30 min, 2) the treatment increased production of NBD-caproic acid, a counterpart of sphingosine, by ceramidase within 2 h, 3) expression of ceramide kinase enhanced the Na3VO4-induced formation of NBD-C1P, and tyrosine kinase inhibitors (herbimycin and genistein) decreased the response, 4) the production of NBD-caproic acid in A549 cells was inhibited by genistein, and 5) the responses for 2 h after Na3VO4 treatment were accompanied by a decrease in the production of NBD-sphingomyelin, not a loss of NBD-ceramide. The improved thin-layer chromatography method was useful for the simultaneous determination of enzymatic activities for ceramide metabolism in cells. Keywords:: ceramide kinase, ceramide-1-phosphate, ceramidase, vanadate, A549 and Chinese hamster ovary (CHO) cells